Legal Uncertainty of Golf Game as Sports and Entertainment Branch in Local Tax Imposition - Prasetio, Dicky Eko; Masnun, Muh Ali; Wedhatami, Bayangsari (Sekolah Tinggi Hukum Bandung, 2024)
The imposition of a golf tax actually raises legal issues related to the status of golf in connection with the imposition of regional taxes. The object of this research is the status of golf as entertainment or a sport and the implications of legal uncertainty related to the imposition of regional taxes. This research is a normative legal study with a historical, legislative, and case approach. The legal materials used include primary legal materials in the form of legislation and court decisions, secondary legal materials in the form of research results such as journal articles and relevant books, as well as non-legal materials such as language dictionaries. The technique for collecting legal materials is conducted through library research by gathering legal materials from libraries as well as collecting legal materials through national and international journal article websites. The analysis of legal materials is conducted prescriptively, emphasizing legal prescriptions or solutions as answers to legal issues in this research. The findings of this research emphasize that the legal uncertainty regarding the status of golf as entertainment and a sport in relation to local tax imposition implies that golf, as a sport, can only be subject to VAT and therefore cannot be subject to local tax. The recommendation from this research is that there needs to be a revision of the legislation in the field of taxation and a clarification that golf can be subject to regional taxes. This research is expected to contribute to the thinking and practice related to the development of tax imposition on golf facilities.